2021
DOI: 10.1016/j.jiac.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in survival and causes of death among people living with HIV: Three decades of surveys from Tokyo, one of the Asian metropolitan cities

Abstract: Introduction: Survival among people living with HIV (PLWH) has dramatically improved in the antiretroviral therapy (ART) era. This is the first study in Asia to describe three decades of surveys on survival and causes of death among PLWH. Methods: We included 1121 HIV-infected patients, categorized into three period groups according to date of first visit: 1986e1996 (Pre-ART); 1997e2007 (Early-ART); and 2008e2018 (Late-ART). Results: Ten-year all-cause mortality has reduced from Pre-ART (49.6/1000 person-years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
10
0
4
Order By: Relevance
“…O mesmo padrão foi encontrado em outros estudos que apontaram o aumento dos óbitos por doenças não def inidoras. 2,16,3…”
Section: Discussionunclassified
See 3 more Smart Citations
“…O mesmo padrão foi encontrado em outros estudos que apontaram o aumento dos óbitos por doenças não def inidoras. 2,16,3…”
Section: Discussionunclassified
“…1 A TARV proporcionou aumento da sobrevida e qualidade de vida das pessoas portadoras do vírus da imunodeficiência humana (HIV) e aquelas com manifestação da síndrome da imunodeficiência adquirida (aids). 2 Esse tratamento levou à ocorrência de óbitos por doenças relacionadas ao avanço da idade ou uso prolongado de TARV, classificadas como doenças não definidoras de HIV/aids, tais como hipertensão arterial, diabetes mellitus, cardiopatias, neoplasias, doenças renais e outras. Desta forma, houve queda dos óbitos por doenças associadas à imunodeficiência que, até então, permitiam o surgimento de doenças oportunistas, estas sim as doenças definidoras de HIV/ aids, caracterizadas pela ocorrência de alguma enfermidade específica entre as pessoas que vivem com HIV/aids (PVHIV), imunodeprimidas em razão do avanço da infecção pelo HIV e da manifestação da aids, a exemplo da pneumonia e da tuberculose.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…While in the early years of ART scale-up high rates of mortality and morbidity were mostly attributed to the occurrence of opportunistic infection (OIs) (9), this trend has changed with the emergence of non-HIV related causes of morbidity and mortality with cardiovascular disease accounting for 11% of these deaths (10)(11)(12). A study from Uganda found 18% sub-clinical atherosclerosis, an indicator of cardiovascular disease, in HIV-positive patients (13).…”
Section: Introductionmentioning
confidence: 99%